Combined treatment of cisplatin and 5-Fluorouracil Induces cell death in ARPE-19 cells through the endoplasmic reticulum stress pathway (Annals of Medical Research, 2021)
Aim: Cisplatin and 5-Fluorouracil have been used for about 50 years as chemotherapy agents. Combination of these two agents is known as PF therapy and is widely used in the treatment of anal, esophageal cancer, head and neck cancer. One of the problems encountered with antineoplastic agents is the rapid and irreversible side effects on non-target cells and organs. It is common that occourence of ocular toxicity by chemotherapy. Materials and Methods: ARPE-19 cell viability and toxicity were determined by performing (MTT)-based colorimetric assays and IC50 values calculated by probit analyses options of SPSS 20 Software. Acridine orange/Ethidium bromide (AO/EB) fluorescent staining was performed to determine structural changes such as cell blebbing and chromatin condensation during the apoptosis process on cells. Images examined under a fluorescent microscope (Zeiss Axio Vert.A1) at 40X magnification with FITC filter for AO and Tex Red filter. And Real-time PCR was performed with ABI Step One Plus and Quant Studio 5 Real-Time PCR systems.Results: PF treatment within 24 hours and 48 hours caused ER stress due to toxic effect and this induced cell death through apoptosis via death receptor signaling and intrinsic pathway in ARPE-19 cells. Conclusion: PF-induced activation of the ER stress mechanism can be used as a novel therapeutic strategy for the prevention of side effects of non-target cells.